2012
DOI: 10.1111/j.1875-595x.2011.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries related to quality of life in two Brazilian adolescent groups: a cross-sectional randomised study

Abstract: Objectives:  To analyse dental caries‐related quality of life (QoL) in adolescent (15–19‐year‐old) subjects in a suburban area (SA) and a downtown area (DA) of Bauru, São Paulo, Brazil, in 2009. Methods:  This was a cross‐sectional, randomised study. The sample consisted of 185 and 147 adolescents from the SA and DA, respectively. The caries index used was that for decayed, missing and filled teeth (DMFT) (World Health Organization criteria). The 14‐item Oral Health Impact Profile (OHIP‐14) was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
5
28
0
10
Order By: Relevance
“…dental caries) during adolescence could affect health-related quality of life (HRQOL). 24,25) Our findings suggested that problematic Internet use could lead not only to mental health problems but also to HRQOL in adolescent group. It is known that addictive behaviors are inversely associated with lower quality of life.…”
Section: Discussionmentioning
confidence: 69%
“…dental caries) during adolescence could affect health-related quality of life (HRQOL). 24,25) Our findings suggested that problematic Internet use could lead not only to mental health problems but also to HRQOL in adolescent group. It is known that addictive behaviors are inversely associated with lower quality of life.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, negative impact of quality of life measured by the OHIP-14 is usually increased by higher DMFT (30).…”
Section: Discussionmentioning
confidence: 99%
“…Para avaliar o impacto das condições de saúde bucal sobre a qualidade de vida dos adolescentes, aplicou-se aos participantes do estudo o questionário Oral Health Impact Profile (OHIP-14), validado no idioma português (14) e utilizado como instrumento para verificar as experiências vivenciadas pelos adolescentes nos últimos 12 meses, segundo metodologia preconizada (15) . O OHIP-14, através de 14 perguntas, permitiu avaliar os seguintes parâmetros ou dimensões na qualidade de vida: limitação funcional, dor física, desconforto psicológico, incapacidade física, incapacidade psicológica, incapacidade social e desvantagem social.…”
Section: Métodosunclassified
“…Assim, classificou-se o impacto geral em: fraco, quando os índices obtidos variaram de 0 a 9; médio, entre 10 e 18; e forte, entre 19 e 28. A avaliação do impacto por domínio ou dimensão seguiu a metodologia utilizada em outro estudo (15) : fraco (≤ 1,33), médio (1,33 < x < 2,67) e forte (≥ 2,67).…”
Section: Métodosunclassified